A 2.5D convolutional neural network for HPV prediction in advanced oropharyngeal cancer. (March 2022) - La Greca Saint-Esteven, Agustina; Bogowicz, Marta; Konukoglu, Ender; Riesterer, Oliver; Balermpas, Panagiotis; Guckenberger, Matthias; Tanadini-Lang, Stephanie; van Timmeren, Janita E.
Abstract: Background: Infection with human papilloma virus (HPV) is one of the most relevant prognostic factors in advanced oropharyngeal cancer (OPC) treatment. In this study we aimed to assess the diagnostic accuracy of a deep learning-based method for HPV status prediction in computed tomography (CT) images of advanced OPC. Method: An internal dataset and three public collections were employed (internal: n = 151, HNC1: n = 451; HNC2: n = 80; HNC3: n = 110). Internal and HNC1 datasets were used for training, whereas HNC2 and HNC3 collections were used as external test cohorts. All CT scans were resampled to a 2 mm 3 resolution and a sub-volume of 72x72x72 pixels was cropped on each scan, centered around the tumor. Then, a 2.5D input of size 72x72x3 pixels was assembled by selecting the 2D slice containing the largest tumor area along the axial, sagittal and coronal planes, respectively. The convolutional neural network employed consisted of the first 5 modules of the Xception model and a small classification network. Ten-fold cross-validation was applied to evaluate training performance. At test time, soft majority voting was used to predict HPV status. Results: A final training mean [range] area under the curve (AUC) of 0.84 [0.76–0.89], accuracy of 0.76 [0.64–0.83] and F1-score of 0.74 [0.62–0.83] were achieved. AUC/accuracy/F1-score values of 0.83/0.75/0.69 and 0.88/0.79/0.68 were achieved on the HNC2 and HNC3 test sets, respectively. Conclusion: Deep learning was successfully applied and validated in two external cohorts to predict HPV status in CT images of advanced OPC, proving its potential as a support tool in cancer precision medicine. Highlights: Infection with HPV in oropharyngeal cancer is captured in CT anatomical imaging. Deep learning can decode HPV status in CT of advanced oropharyngeal cancer. Deep learning holds potential as an ancillary diagnostic tool in clinical-decision support systems.